Socialization of Low-Salt Diet in Hypertension Patients within Puskesmas Karang Anyar - Panjaitan, Raini; Sitepu, Sari Desi Esta Ulina; Rambey, Harrys; Angraini, Salmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Hypertension is a type of non-communicable disease and is a health problem that often occurs in society and even around the world. The prevalence of hypertension can increase due to a lack of knowledge about the appropriate diet for hypertension sufferers. A low-salt diet is an appropriate diet for hypertension sufferers to regulate the amount of sodium intake in the body. This service activity aims to increase knowledge about low-salt diets. Method of implementing low salt diet outreach by the community service team using leaflet media. The leaflet was distributed to all activity participants. The number of participants in this PkM activity was 35 people. The implementation carried out by the PkM team consisted of lecturers and students from the Nutrition Study Program, Nursing Study Program, and Midwifery Study Program and collaborated with Karang Anyar Community Health Center partners. Based on the results of the activity, of the 35 participants who attended the service activity, the characteristics of the frequency of participants' blood pressure checks were obtained, the majority of participants had a history of grade II hypertension, 15 people (43.0%). Then there were 12 people in the level II hypertension category (34.2%), followed by the pre-hypertension category with 8 people (22.8%). Based on the results of socialization activities after carrying out before and after evaluations of increasing knowledge for 35 participants, that number was 23 (65.8%). This PkM activity concludes that a lack of knowledge about a low-salt diet is the cause of the high number of hypertension sufferers and a lack of knowledge about the types of food that are recommended and not recommended for hypertension sufferers. So educational programs are needed to increase public understanding about low-salt diets.